Development of a Continuous Pulsed Electric Field (PEF) Vortex-Flow Chamber for Improved Treatment Homogeneity Based on Hydrodynamic Optimization - Schottroff, Felix; Knappert, Justus; Eppmann, Pauline; Krottenthaler, Anna; Horneber, Tobias; McHardy, Christopher; Rauh, Cornelia; Jaeger, Henry (Frontiers in Bioengineering and Biotechnology, 2020)
Pulsed electric fields (PEF) treatment is an effective process for preservation of liquid products in food and biotechnology at reduced temperatures. Therefore, it enables the retention of higher levels of heat-labile constituents or an enhanced level of microbial inactivation based on electroporation. However, PEF treatment is accompanied by a dissipation of electrical energy resulting in an increase of product temperature, depending on the treatment intensity. Especially for continuous treatments performed on (semi) industrial scale, treatment chamber designs are used that compromise homogeneous treatment conditions. Inhomogeneities of the electric field within the treatment chamber may occur, leading to inhomogeneous temperature fields and associated temperature peaks. In combination with a non-uniform flow velocity and residence time, a wide distribution of occurrence and intensity of electroporation for different locations within the treatment chamber and thermal over-processing may occur. For this reason, a specific treatment chamber was designed in order to improve the residence time distribution and to reduce local temperature peaks, therefore increasing treatment homogeneity. This was accomplished by a divided inlet into the chamber, consequently generating a swirling flow (vortex). Inlet angles were optimized using computational fluid dynamics (CFD), in order to obtain a more homogeneous treatment conditions. The new design was consequently experimentally compared to a conventional co-linear setup, taking into account inactivation efficacy of Microbacterium lacticum as well as retention of heat-sensitive alkaline phosphatase (ALP). Results showed an increase in M. lacticum inactivation by the vortex configuration and more homogeneous treatment conditions. Therefore, the new setup can contribute to optimize PEF treatment conditions and to further extend PEF applications to currently challenging products.